INVESTIGAÇÃO DO EFEITO DO TRITERPENO 3Β,6Β,16Β-TRIHIDROXILUP-20(29)-ENO (TTHL) SOBRE A PROLIFERAÇÃO DE QUERATINÓCITOS HUMANOS (HACAT) - Dykstra, Stefanie Nolte (2013)
Introduction: Psoriasis is a skin inflammatory disease characterized by keratinocytes hyperproliferation and their incomplete differentiation in the epidermis. Treatment aims to reduce the psoriatic plaques formation; however, many therapeutic regimens do not produce satisfactory results. Searching for new alternatives, this study evaluated the possible effect of the TTHL compound, isolated from the ethanolic extract of Combretum leprosum, on HaCaT proliferation.Methods: The cellular viability was assessed 24 hours after the treatment with different concentrations of TTHL through MTT and neutral red methods. To evaluate the TTHL anti-proliferative activity, the cells were treated with different concentrations of TTHL, in alternate days (96 hours) and analyzed through MTT and Cyquant methods. The cell cycle was evaluated by flow citometry. The possible toxicity by the topical application of the TTHL (0.3 mg/ear) was assessed in vivo, through skin atrophy, by measuring ear thickness of animals and histology.Results: The MTT assay showed, after 24 hours, that TTHL presents cytotoxic activity in HaCaT cells, at the concentrations of 5, 7, 9 and 10 μM, decreasing, respectively, 53.54, 89.53, 89.69 and 90.30 ± 5.84% the cellular viability compared to the control group. The neutral red assay, in the same concentrations, decreased 39.83%, 48.67%, 47.78% and 50.44 ± 4.42%, respectively. In the cellular proliferation assay, the 5, 7 and 10 μM concentrations decreased 24.27%, 59.25% and 82.30% ± 5.96% the cells number, as showed in the MTT method, and 30.30%, 59.59% e 90.90% ± 6.03% as showed in the Cyquant method. The cell cycle assay showed that, at the concentrations of 5, 7 and 10 μM, the non-viable cells number was higher and statistically significant when compared to the control group. Through the skin atrophy assay was possible to conclude that TTHL does not cause atrophy.Conclusion: TTHL is capable of reducing cell viability. These data suggest that TTHL might be a possible tool for the treatment of hyperproliferative diseases, among them, psoriasis. However, additional studies are needed to verify the action mechanism and triterpene safety.